Deformation Mechanisms in Metastable Austenitic TRIP/TWIP Steels under Compressive Load Studied by in situ Synchrotron Radiation Diffraction. Issue 5 (26th November 2018) - Ullrich, Christiane; Martin, Stefan; Schimpf, Christian; Stark, Andreas; Schell, Norbert; Rafaja, David
Abstract : The stress–strain behavior of austenitic steels showing the TRIP/TWIP effect can be adjusted in a broad range by the addition of suitable alloying elements. Although the underlying deformation mechanisms are reasonably understood, the existing models often fail, in particular when the density of microstructure defects is high and when individual microstructure defects and features start to interact. For a micromechanical description of the material behavior involving possible interactions between different microstructure defects in austenite (dislocations, stacking faults) and newly developed phases, a detailed in situ microstructure characterization of the material under load is needed. In this study, the in situ experiments are performed using synchrotron diffraction during uniaxial compression. The materials under study are Cr–Mn–Ni steels with different Ni contents (3, 6, and 9 wt%) and thus different stacking fault energies (7.5, 16.7, and 24.3 mJ m −2 ). The in situ measurements reveal information about the martensitic phase transformations and about the development of the defect structure of austenite. The latter is concluded from the broadening and shift of diffraction lines and interpreted in terms of the squared microstrain, which is proportional to the dislocation density, and the stacking fault probability. The changes in the phase composition and defect structure are correlated with the residual elastic lattice strain. Abstract : The deformation mechanisms in 16Cr–7Mn–xNi steels with different Ni contents (3, 6, and 9 wt%) and thus with different stacking fault energies are investigated using in situ synchrotron radiation diffraction under uniaxial compression. The evolution of microstructure defect densities and martensitic phase transformation are tracked and their correlation and effect on the mechanical behavior are described.